Aerobic:anaerobic characteristics of the four competitive strokes
The less economical a stroke, the more anaerobic is the energy component. Butterfly and breaststroke are more demanding anaerobically (lactates will be higher) than crawlstroke and backstroke. The VO2max of top swimmers does not differ between strokes. It is the efficiency of action demanded by the stroking limitations which produces the energy-requirement differences. The percent contribution of the aerobic and anaerobic systems differ for the 100 and 200 m distances. The contributions are 40:60 for the shorter and 60:40 for the longer. Consequently, the nature of energy system training should differ for the two events. Swimmers with larger muscle mass and greater anaerobic capacities are likely to be more successful in breaststroke and butterfly events. Implication: The type of training for these strokes should contain more anaerobic work than usually afforded in crawlstroke centered programs. Specific anaerobic training parameters, such as longer (1+ min) rest periods in interval sets, in-water power training, and specific stroke attention to propelling efficiency are major emphases to be considered. (ICAR 1990-91 Report)